The influence of government shareholding on dividend policy in Malaysia - Philip Sinnadurai; Ravichandran K. Subramaniam; S. Susela Devi (International Journal of Financial Studies, 2021)
We investigate the association between dividend policy and government shareholding, using Malaysian data. We hypothesize a positive association. We contribute to the literature about dividend policy. Unique features of our study include adaptations to the Malaysian institutional setting, with respect to usage of dividend relevance theory, research methodology, and data collection. The methodology entails two-stage least squares regressions. Dividend payout and dividend yield are the dependent variables in tests of the research hypothesis. The independent variable of interest measures ownership by government-related institutional investors. The sample comprises 1190 company-years, over the investigation period 2006-2013. The results support our hypothesis. The evidence suggests that this support principally emanates from companies with low-quality corporate governance.
Keywords: G35; G34; 330; dividend policy; government shareholding; Malaysia